Bri2 BRICHOS client specificity and chaperone activity are governed by assembly state - Gefei Chen (Nature Portfolio, 2017)
The BRICHOS domain is a chaperone that can act against amyloid-β peptide fibril formation and non-fibrillar protein aggregation. Here the authors use a multidisciplinary approach and show that the Bri2 BRICHOS domain has qualitatively different chaperone activities depending on its quaternary structure.